Effects of Environmental Quality on Human Health Status in Nigeria - OKOGOR, CHUKS (Acta Universitatis Danubius. Œconomica, 2022)
The Quality of the environment is central to the existence of life, and where the environment in a country is of high quality, human beings as well as plants and animals will live longer, enjoy a life of improved quality, and hence sustainable development may be achieved. Deterioration in environmental quality is related to serious human health issues and this is the reason why the relationship between environmental quality and health is being investigated both by researchers and by policy makers. This study therefore examined the effects of environmental quality on human health status using the Ordinary Least Square estimation techniques. The findings of this show the existence of a longrun relationship among health proxied by life expectancy and the included explanatory variables. The result also shows that CO2 emission an indicator for environmental quality significantly reduces life expectancy. Moreso, income and the linear combination of access to improved water source and access to improve sanitary facility significantly improves life expectancy. We conclude that it is important for Nigeria to strengthen environmental regulations meant to improve people’s access to quality water and sanitary facilities among improved income aimed at improving health status.